FINANCING OF BUDGET DEFICITS AND INFLATION IN NIGERIA, 1966-85 (1995)
In a federal system of government, it may not be sufficient to study the inflationary effect of government reliance on money creation as a major means of financing expenditure. This is particularly so as some level of government besides the central authority may finance its deficit without recourse to money creation but in ways that may ultimately augment the money supply. There is therefore the imperative need to study the interaction between budget deficits and inflation in the Nigerian economy taking into account the various financing options. The stock of money is considered to be affected by the net claims of the central bank and commercial banks on the government. The public finance approach to inflation with its emphasis on the government budget constraint provides the analytical framework on which a monetarist model of inflation is formulated. The model is estimated using annual data for the period 1966-85. Equations are specified to explain price determination, money supply, high-powered money, government net indebtedness to the banking system, revenue, and expenditure. Besides, identities relating to formation of expectations about inflation and the budget constraint are set out. Since the constructed model was over-identified based on the rank and order conditions for identification, the two-stage least sguares technique was used in the estimation. The empirical results show that government borrowing from the central bank as well as the banking system serve to expand the money supply and exert upward pressure on the price level. However, a given percentage increase in the debt holdings of the central bank greatly affects the money supply and price level more than an equivalent percentage increase in the net claims of commercial banks on the government. Debt holdings by the nonbank public was found to have similar macro- economic effects as private wealth. However, because the positive effect on aggregate demand through this financing source is through a channel different from money supply and more importantly its relative insignificance, this phenomenon generally known as "Wealth-Savings Relation" was not incorporated in the analytical model.